Determinants of the success of international assignees as knowledge transferors: a theoretical framework - Bonache, Jaime; Zarraga-Oberty, Celia (Taylor & Francis, 2008)
Drawing on previous work in the knowledge management literature, this article develops a conceptual framework to analyse the cause and effects of international assignments as a knowledge transfer mechanism. In examining the characteristics of knowledge transferred within multinational companies (MNCs) the use of international assignees is explained and justified. The article also identifies the factors influencing the success of international assignees as knowledge transferors. It is argued that, in addition to the specific characteristics of the knowledge involved, transfer success will be affected by three sets of human-related factors: abilities and motivation of international staff; abilities and motivation of local employees; and the relationship between local and international staff. The article concludes by discussing some management initiatives helping to trigger the human-related factors.
Keywords: International assignments; Knowledge transfer; Expatriation; Multinational corporation